Unveiling school effectiveness: Progress 8, parental choices and closing the achievement gap - Jack Britton; Damon Clark; Ines Lee (Institute for Fiscal Studies (IFS), 2023)
We show that Progress 8 is a reliable measure of school effectiveness and that parents often do not apply to their most effective local school.
Keywords: 330; Education and skills; Inequality; Education; Schools; Skills